2022
DOI: 10.1136/bmj-2021-068788
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent intervention to prevent mobility disability in frail older adults: randomised controlled trial (SPRINTT project)

Abstract: ObjectiveTo determine whether a multicomponent intervention based on physical activity with technological support and nutritional counselling prevents mobility disability in older adults with physical frailty and sarcopenia.DesignEvaluator blinded, randomised controlled trial.Setting16 clinical sites across 11 European countries, January 2016 to 31 October 2019.Participants1519 community dwelling men and women aged 70 years or older with physical frailty and sarcopenia, operationalised as the co-occurrence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
117
1
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 132 publications
(149 citation statements)
references
References 47 publications
3
117
1
6
Order By: Relevance
“…Exercise is a subset of physical activity, being planned, structured and repetitive [ 150 ], and its benefits have been extensively studied. Exercise improves different parameters in older adults, such as strength [ 153 , 154 ] and physical function [ 154 , 155 ], and reduces disability [ 28 , 30 ], as well as preventing falls and fall-associated injuries [ 156 ], demonstrating that lengthy interventions are safe [ 157 ]. Even in older adults who meet the sarcopenia criteria, physical exercise significantly improves strength (assessed by grip strength, knee extension and chair test), physical functioning (timed up and go test and gait speed) and muscle mass [ 158 ].…”
Section: Impact Of Physical Activity/exercise On Aged Skeletal Muscle...mentioning
confidence: 99%
See 2 more Smart Citations
“…Exercise is a subset of physical activity, being planned, structured and repetitive [ 150 ], and its benefits have been extensively studied. Exercise improves different parameters in older adults, such as strength [ 153 , 154 ] and physical function [ 154 , 155 ], and reduces disability [ 28 , 30 ], as well as preventing falls and fall-associated injuries [ 156 ], demonstrating that lengthy interventions are safe [ 157 ]. Even in older adults who meet the sarcopenia criteria, physical exercise significantly improves strength (assessed by grip strength, knee extension and chair test), physical functioning (timed up and go test and gait speed) and muscle mass [ 158 ].…”
Section: Impact Of Physical Activity/exercise On Aged Skeletal Muscle...mentioning
confidence: 99%
“…Alternatively, due to the multiorgan and biological systems that are involved in the frailty syndrome, the inclusion of different types of exercise, such as strength, aerobic, balance or flexibility, could be the best intervention for this type of patient [ 30 , 154 , 169 , 170 , 171 ]. In line with this, recent research has been published with data from the SPRINTT study (Sarcopenia and Physical Frailty in Older People: Multi-component Treatment Strategies) conducted in community-dwelling older adults with a mean age of 78.9 years with physical frailty who also met the sarcopenia criteria.…”
Section: Impact Of Physical Activity/exercise On Aged Skeletal Muscle...mentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the results were not adjusted for numerous covariables, including physical activity levels [62], oral health [65], and the presence of comorbidities [66]. Particularly, recent findings from the SPRINTT project showed that a multicomponent intervention, which involved a daily protein intake of at least 1.0-1.2 g/kg of BW and a physical activity intervention, reduced the incidence of mobility disability in older adults with physical frailty and sarcopenia [67]. Thirdly, the limited number of included studies did not allow meta-regression, dose-response, risk of bias, or "trim and fill" analyses to be conducted.…”
Section: Discussionmentioning
confidence: 99%
“…Instructor-led gymnastics classes are reportedly safer and more effective than self-directed efforts and self-assessment, and are better able to improve physical function than home-based exercise programs [ 2 , 4 ]. In addition, classes that add nutritional counseling and other services [ 5 ] and programs such as the “In Balance program” in the Netherlands [ 6 ], which includes an educational component and physical exercises focused on balance and muscle strength, are considered to be more effective. However, widespread implementation of these classes is unlikely in the near future because of systemic shortfalls in facilities, staffing, and funding, and insufficient performance as per the Cost Performance Index.…”
Section: Introductionmentioning
confidence: 99%